Changes in Parents' Emotion Regulation and Psychological Reflection After a Journaling Therapy Program - Wise Rahmawan; Rindang Wahjuningtijas; Wenny Wulandari; Miskanik Miskanik; Farouq Fathurrahman (Journal of Education and Counseling (JECO), 2026)
Parenting adolescents requires parents to manage their emotions and reflect on their parenting experiences. Journaling therapy is one type of expressive writing that may help parents become more aware of their emotions and thoughts. This study aimed to describe changes in parents' emotion regulation and psychological reflection after participating in a journaling therapy program. This study used a quantitative approach with a one-group pretest–posttest design. The participants were 56 parents of students at SMP Muhammadiyah Pabuaran. Data were collected using an emotion regulation scale and a psychological reflection scale. The data were analyzed using descriptive statistics by comparing the mean scores before and after the program. The mean score of emotion regulation increased from 28.47 before the program to 33.85 after the program. The mean score of psychological reflection also increased from 27.96 to 34.12. These results show higher mean scores after the journaling therapy program. Journaling therapy may be used as an alternative activity in school parenting programs to support parents' emotion regulation and psychological reflection.